Synthesis of charged silica films of porous structure - Zharkikh, Yu.S.; Lysochenko, S.V.; Pylypenko, O.A.; Tretyak, O.V. (Functional Materials, 2008)
A new technique has been proposed to obtain thin charged dielectric silica films with porous structure on a Si surface. The film composition and charge state of the dielectric/semiconductor system obtained have been studied. Thickness and porosity degree of the synthesized films have been estimated. The films have been shown to be similar in structure to silica aerogel. The films using in the semiconductor microelectronics, in particular, for sensors and solar cells is proposed.